تنوير الرضا كآلية وقائية لحماية المتعاقد الضعيف من اختلال التوازن المعرفي - دنيدني, سليمة (University of Eloued جامعة الوادي, 2021)
إن الاختلال والتفاوت الواضح بين المتعاقدين في العقود الاستهلاكية، خلق أزمة توازن مصدرها التفوق المعرفي بين متعاقد على حساب المتعاقد الآخر ، عجزت النظرية العامة للعقد في مواجهته، خاصة أنها لم تقتصر في جانبها الحمائي سوى على تصحيح الأوضاع الظاهرة الخلل، تحقيق الحماية العلاجية بناءا على شروط طالما كانت ميزتها الأساسية الصرامة في إثباتها، لذلك كان لابد على المشرع أن يواجه التفوق المعرفي من خلال تجسيد آليات تضمن الحماية الوقائية للمتعاقد الضعيف وتحفظ له الثقة التي يقتضيها الضمير في المعاملات العقدية المختلفة، وتعلق الأمر بفرض التزام بالإعلام على المتعاقد القوي، وتكريس مهلة التفكير كوسيلة في يد المتعاقد الضعيف، والغاية من كلاهما ضمان الحماية الوقائية للمتعاقد الضعيف من اختلال التوازن المعرفي، من خلال تحسين رضاه وتنويره، بدلا من الضمانات والآليات العلاجية التي تكفلت نظرية عيوب الرضا بتبنيها. Abstract: The apparent imbalance and disparity between the contracting parties in consumer contracts have created a balance crisisdue to the cognitive superiority of one contractor at the expense of the other. Unfortunately, the general contract theory failed to solve this problem, namely becauseit was limited to correcting the apparent defect conditions, achieving remedial protection based on ineffective rigorous conditions. Therefore, it was necessary for the legislator to overcome this cognitive superiority by embodying mechanisms that guarantee the preventive protection of the vulnerable contractor and preserve his conscience reliability required in the various contractual transactions. The matter of cognitive balance ealso depends on imposing the principle of commitment to information on the strong contractor, and giving a reflection period to the vulnerable contract. These procedures may help protecting the vulnerable contractor from an ultimate cognitive imbalance and improve his satisfaction and enlightenment, instead of the guarantees and remedial mechanisms adopted by the theory of satisfaction defects.
Enlighten Satisfaction as a Preventive Mechanism for Protecting the Vulnerable Contractor from Cognitive Imbalance
مقال
Keywords: الالتزام بالاعلام ; مهلة التفكير ; التوازن المعرفي ; تنوير الرضا ; المتعاقد الضعيف; Enlighten Satisfaction; Vulnerable Contractor; Commitment to Information; Cognitive Balance; Reflection Period